2013
DOI: 10.1103/physrevstper.9.010117
|View full text |Cite
|
Sign up to set email alerts
|

Students’ epistemological beliefs, expectations, and learning physics: An international comparison

Abstract: It has been established by physics education researchers that there is a correlation between the learner's behavior, their epistemological beliefs with which they come to the classrooms, and their success in a course. This study of Indian students and teachers explores expectations and beliefs in learning physics at the secondary and tertiary levels by making use of the Maryland Physics Expectation (MPEX) survey, which has been tested for both its validity and its reliability. The MPEX was administered to a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
3
18
0
6
Order By: Relevance
“…Searching the literature, we found that in work stating both favorable and unfavorable responses in their postinstruction MPEX scores, the pattern repeated to within 3% to 5% for all introductory physics courses regardless of instructional type. We found similar results for CLASS data with both favorable and unfavorable responses reported [4,7,[13][14][15]. Figure 2 shows a favorable versus unfavorable Redish plot using the sources that we found with lines indicating the 15% and 25% unfavorable bounds.…”
Section: Question 1: What Are the Overall Results By Instructor On Thsupporting
confidence: 77%
See 2 more Smart Citations
“…Searching the literature, we found that in work stating both favorable and unfavorable responses in their postinstruction MPEX scores, the pattern repeated to within 3% to 5% for all introductory physics courses regardless of instructional type. We found similar results for CLASS data with both favorable and unfavorable responses reported [4,7,[13][14][15]. Figure 2 shows a favorable versus unfavorable Redish plot using the sources that we found with lines indicating the 15% and 25% unfavorable bounds.…”
Section: Question 1: What Are the Overall Results By Instructor On Thsupporting
confidence: 77%
“…There is a body of literature dedicated to the study of student beliefs about their role in the physics classroom and how such beliefs affect student engagement and achievement in the physics course [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. These are instrumental in our understanding of how student expectations of learning may change during the course of an introductory physics course, concentrating on student favorable responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the pre and post results correlated with student gains on physics concept tests, signifying a possible causal connection between epistemology and conceptual learning in physics. Similar findings have been frequently reported across student populations from different nations [14,18].…”
Section: Theoretical Backgroundsupporting
confidence: 77%
“…For example, it is widely agreed that students should, over the course of taking a science class, come to understand science learning as an active process of meaning making rather than a passive process of receiving information [14,15]. Within undergraduate physics courses, scholars are dedicated to pursuing this epistemological goal [15][16][17] and have developed a variety of instruments to examine the success of instructional interventions in achieving it [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%